Socioeconomic surveys on private tanker water markets in Jordan: Objectives, design and methodology - K. Sigel; C. Klasser; H. Zozmann; S. Talozi; B. Klauer; E. Gawel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
[Background and survey objectives] In Jordan, which is one of the water poorest countries in the world, water supply is generally intermittent. As a consequence, water supplied by private water vendors via tanker trucks is an important source of drinking water for many Jordanians. The impacts of partially illegal private tanker water markets on sustainable water supply in Jordan's cities are manifold and complex. The markets significantly contribute to the welfare of commercial establishments and households. However, they also have strong negative impacts on sustainability for example through groundwater depletion. A deepened understanding of emergence, spreading, and functioning of private tanker water markets in Jordanian cities is a precondition for developing policies and interventions towards more sustainable water supply regimes. The study of publicly available data and reports on private tanker water markets in Jordan revealed that there is a need for empirical data and investigations on the supply side of private tanker water as well as on the demand side, especially in terms of commercial establishments who are the major customers of tanker water within cities. Against this background, in the period from September 2015 to October 2016 five mostly quantitative surveys were conducted within the Stanford-led Belmont Forum "Jordan Water Project (JWP)" in order to collect socioeconomic as well as physical and technical data about private tanker water supply and demand in three different Jordanian cities. The objective of the surveys is to provide an empirical basis for two major fields of investigation: * Socioeconomic studies (e.g. market analyses) on the impacts of private tanker water markets on water supply in the city of Amman with a focus on sustainability issues. * Modelling studies on private tanker water markets in Jordan as part of a hydro-economic model on freshwater resources sustainability in Jordan (e.g. estimation of demand functions for piped and tanker water of commercial establishments, simulation of partially illegal markets of private tanker water providers, spatial statistical analyses of commercial water consumption). Jordan's capital Amman was the location of three surveys targeted at the following key market actors of tanker water: (i) operators of private wells selling water to private water tankers, (ii) water tanker drivers purchasing water from private wells and delivering the water throughout the city of Amman and (iii) commercial establishments using piped and/or tanker water. In order to broaden the empirical basis for advanced modelling studies and simulations on the country level the survey with commercial establishments was repeated in a slightly modified version with (iv) commercial establishments in the city of Irbid and (v) commercial establishments in the city of Ajloun. In this discussion paper the design and methodology of all five surveys is described in detail. For the Amman surveys in addition the survey locations and the spatial distribution of interviews are specified and represented by GIS maps.
Keywords: 330